Notch regulates the angiogenic response via induction of VEGFR-1 - Funahashi, Yasuhiro; Shawber, Carrie J; Vorontchikhina, Marina; Sharma, Anshula; Outtz, Hasina H; Kitajewski, Jan (Vascular Cell, 2010)
Abstract   Notch is a critical regulator of angiogenesis and arterial specification. We show that ectopic expression of activated Notch1 induces endothelial morphogenesis in human umbilical vein endothelial cells (HUVEC) in a VEGFR-1-dependent manner. Notch1-mediated upregulation of VEGFR-1 in HUVEC increased their responsiveness to the VEGFR-1 specific ligand, Placental Growth Factor (PlGF). In mice and human endothelial cells, inhibition of Notch signaling resulted in decreased VEGFR-1 expression during VEGF-A-induced neovascularization. In summary, we show that Notch1 plays a role in endothelial cells by regulating VEGFR-1, a function that may be important for physiological and pathological angiogenesis.